The relationship between parental involvement, the role of counselors, student abilities and socioeconomic status towards the interest in continuing studies in high school students in Sukabumi City - Kresna Ningsih Manik; Bhenu Artha (Westscience Press, 2023)
This study aims to investigate the relationship between parental involvement, the role of counselors, student abilities, and socioeconomic status to the interest in continuing studies among high school students in Sukabumi City. A total of 327 students from four high schools in Sukabumi City participated in the study. Data were collected using a self-report questionnaire that assessed parents' level of engagement, counselor support, student ability, socioeconomic status, and students' interest in continuing their studies. The results showed that these four factors have a significant relationship with students' interest in continuing their studies. The findings suggest that increasing parental engagement and counselor support, as well as providing opportunities and resources to students with lower academic ability and socioeconomic status, can increase students' interest in continuing their studies